2013
DOI: 10.1002/app.39121
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and gas‐permeation properties of crosslinked diacetylene‐containing polymer membranes from ferulic acid

Abstract: Thermally and UV crosslinked poly[propargyl(3‐methoxy‐4‐propargyloxy) cinnamate] (PPOF) were investigated in terms of their physical, thermal, optical, and gas‐permeation properties. The crosslinked membranes had high gel contents because of the formation of a diacetylene network. The wide‐angle X‐ray diffraction patterns showed that all of the membranes were amorphous in structure, regardless of the type of crosslinking reaction. The membrane density increased after the crosslinking reaction; this suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…[7][8][9] Polymers containing FA in the main chain have also been proposed to obtain materials for sensing and/or imaging applications. [10][11][12][13][14][15][16] Aggregation induced emission (AIE) in biocompatible uorophores have gained much attention in recent years since AIE compounds, being weakly emissive or non-emissive in solution due to free intramolecular motions, become good emitters upon aggregation and therefore represent a class of excellent uorescent bioprobes. 17 The glycosaminoglycan hyaluronic acid (HA, hyaluronan) plays important roles in human body.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Polymers containing FA in the main chain have also been proposed to obtain materials for sensing and/or imaging applications. [10][11][12][13][14][15][16] Aggregation induced emission (AIE) in biocompatible uorophores have gained much attention in recent years since AIE compounds, being weakly emissive or non-emissive in solution due to free intramolecular motions, become good emitters upon aggregation and therefore represent a class of excellent uorescent bioprobes. 17 The glycosaminoglycan hyaluronic acid (HA, hyaluronan) plays important roles in human body.…”
Section: Introductionmentioning
confidence: 99%
“…The development of functional biobased polymer materials has received much attention because of environmental concerns in recent years . Natural lacquer is a natural polyphenolic compound and is well known as a traditional natural crosslinked polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Besides thermal cross-linking property, highly reactive propargyl ether-terminated monomers can be used in the preparation of diacetylene-containing polymers by means of oxidative coupling chemistry under oxygen atmosphere with copper (I) chloride (CuCl) as the catalyst. [33][34][35][36] These obtained polymers can similarly undergo cross-linked polymerization under ultraviolet irradiation or by annealing at a definite temperature, and they exhibit enhanced mechanical properties and thermostability because of the volume contraction in the covalent coupling of adjacent diacetylene units. [35][36][37][38][39][40] In recent years, several correlative research studies have been reported on the synthesis and characteristics of diacetylene-containing polymers, for example, thermal properties and mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] These obtained polymers can similarly undergo cross-linked polymerization under ultraviolet irradiation or by annealing at a definite temperature, and they exhibit enhanced mechanical properties and thermostability because of the volume contraction in the covalent coupling of adjacent diacetylene units. [35][36][37][38][39][40] In recent years, several correlative research studies have been reported on the synthesis and characteristics of diacetylene-containing polymers, for example, thermal properties and mechanical strength. [38][39][40][41] Many of the cured products were characterized by good mechanical and thermal properties and chemical resistance.…”
Section: Introductionmentioning
confidence: 99%